The The Role of Sufi Values in Indonesian Music as a Medium for Islamic Da'wah - Kaplan, Muhammad Nur; Zarkasyi, Arif Afandi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This article discusses the influence of Sufism on Indonesian music and its role in the spread of Islam within Indonesian society. Initially, Indonesia was primarily associated with traditional religions like Buddhism and Hinduism until Sufism, introduced by Yemeni traders, helped facilitate the acceptance of Islam. Sufism and Islam became intertwined, significantly shaping Indonesian identity. Key figures, such as the Nine Saints, propagated Islamic values through various means, including music, which serves as a universal art form transcending sects. This integration led to a significant transformation in Indonesian music, incorporating Islamic themes that resonate during religious occasions like Eid and Ramadan. The current research aims to further explore the specific impact of Sufism on Indonesian music, using a combination of deductive and analytical methods, differing from the previous studies' methodologies. This comprehensive approach seeks to elucidate the nuanced relationship between Sufism and the musical landscape in Indonesia.